Mental Health Dynamics and Emotional Intelligence Among Generation Z: A Systematic Review and Bibliometric Analysis of Authoritative Parenting and Work Motivation - Surana, Muhammad Arif; Widhiastuti, Hardani; Dewi, Rusmalia (CV. Tripe Konsultan, 2025)
Mental health and emotional intelligence among Generation Z have become critical issues amid social pressures, digital transformation, and the increasingly complex demands of the workplace. This study aims to systematically examine the relationship between mental health, emotional intelligence, authoritative parenting, and work motivation, as well as to map the development and academic structure of this topic. The research subjects consisted of scientific articles obtained from the Scopus database through a keyword-based systematic search using specific inclusion criteria, resulting in 115 relevant articles for analysis. This study employs a qualitative approach through a systematic literature review combined with bibliometric analysis. Data were collected through the identification, screening, and selection of articles based on the PRISMA procedure, then analyzed using content analysis techniques and visualized with Vosviewer software to map networks, clusters, and relationships between concepts. The results indicate a significant increase in publications related to mental health and emotional intelligence among Generation Z, with a dominant focus on issues of anxiety, depression, burnout, and emotional regulation. However, the variables of authoritative parenting and work motivation remain underrepresented in the existing research framework. In conclusion, this study confirms the existence of a conceptual gap that opens opportunities for the development of an integrative model linking family factors, emotional competence, and Generation Z’s work readiness. The implications of this study provide theoretical contributions to the development of psychological and educational research, as well as practical contributions to the formulation of educational strategies, parenting approaches, and policies for improving the mental health of the younger generation.